Science Education: on the agenda of the Library of Alexandria. - Elmikaty, Hoda S. (Museum International, 2005)
Explains that the Science Centre (SC) at the Library of Alexandria, Egypt, was set up in the belief that curiosity, knowledge, and appreciation of the sciences are essential to the health and survival of the individual, the community and the planet. Excellent and dynamic educational exhibits and programs; Aspiration to be a national model for science education.